The Perceived Impact of MBA Degree on Career and Skills Development: An Explanatory Research Comparing French and GCC Students - Saïd, Karim; Alsultanny, Yas (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2019)
Relying on two diverse samplings of MBA students – one from an international French business school and the other from a university based in Bahrain that recruits students from the Arabian Gulf countries – our article analyzes the relationship between the MBA students’ career goals and their nationality. Our key findings highlight that nationality has little effect on graduate students' motives for pursuing education, their perception of the expected program outcomes and their career perspectives. Other findings, however, reveal some differences based on nationality, the most significant being program criteria choices in relation to career goals and the expected skills students wished to acquire.